ChemInform Abstract: Ruthenium(V) Oxides from Low‐Temperature Hydrothermal Synthesis. Issue 27 (8th July 2014) - Hiley, Craig I.; Lees, Martin R.; Fisher, Janet M.; Thompsett, David; Agrestini, Stefano; Smith, Ronald I.; Walton, Richard I.
Abstract Ca1.5Ru2O7 (I), SrRu2O6 (II), and Ba2Ru3O9(OH) (III) are hydrothermally synthesized from aqueous mixtures of KRuO4 and MO2 (M: Ca, Sr, Ba; autoclave, 200 °C, 24 h).